Social responsibilities and their impact on improving financial performance in Libyan industrial companies operating in Misrata. (Journal of Academic Research, 2025)
The study aimed to identify the impact of social responsibility on improving financial performance in Libyan industrial companies operating in Misrata. To achieve the study objectives، a descriptive and analytical approach was adopted. A questionnaire was designed for the study، and (60) questionnaires were distributed to the study population، consisting of all individuals working in senior management، financial and administrative departments، internal audit departments، and quality departments within Libyan industrial companies operating in Misrata. The aim was to obtain the necessary information. This data was analyzed using the statistical analysis program (SPSS)، and the study's probabilities were tested.The study concluded that there is a statistically impact of social responsibility across its four dimensions (economic، ethical، legal، and charitable) on improving financial performance (return on investment، market share، sales growth، return on